Recurrent Tc-99m Sestamibi Emboli in the Lungs Revealed on Consecutive Rest and Stress Single-Photon Emission Computed Tomography/Computed Tomography Myocardial Perfusion Images - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
Many causes of incidental focal uptake on raw data images using myocardial perfusion imaging, including malignant diseases, metastatic processes, benign pathologies, and physiological conditions, have been reported in the literature. However, iatrogenic Tc-99m sestamibi emboli have not yet been reported. Herein, we demonstrated iatrogenic Tc-99m sestamibi embolization on consecutive rest and stressed myocardial perfusion images at different locations.
Keywords: Tc-99m sestamibi; iatrogenic emboli; myocardial perfusion imaging; single-photon emission computed tomography/computed tomography; FOCAL PULMONARY UPTAKE; SCINTIGRAPHY; SPECT/CT